2014
DOI: 10.1115/1.4026809
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Nonreacting Combustor Simulator With Swirl and Temperature Distortion With Experimental Validation

Abstract: Nonuniform combustor outlet flows have been demonstrated to have significant impact on the first and second stage turbine aerothermal performance. Rich-burn combustors, which generally have pronounced temperature profiles and weak swirl profiles, primarily affect the heat load in the vane but both the heat load and aerodynamics of the rotor. Lean burn combustors, in contrast, generally have a strong swirl profile which has an additional significant impact on the vane aerodynamics which should be accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The design of the simulator is described in Refs. [32,33]. The integration and commissioning of the combustor simulator in the OTRF was described by Adams et al [34].…”
Section: Methodsmentioning
confidence: 99%
“…The design of the simulator is described in Refs. [32,33]. The integration and commissioning of the combustor simulator in the OTRF was described by Adams et al [34].…”
Section: Methodsmentioning
confidence: 99%
“…Hall et al [18] reported the first design of a fully annular leanburn combustor simulator. This simulator, which is the focus of this study, was designed for use in the OTRF using an unsteady Reynolds-averaged Navier-Stokes (URANS) computational fluid dynamics (CFD) approach.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the commissioning in the OTRF of the leanburn combustor simulator developed by Hall et al [18]. The simulator has been modified with respect to the configuration described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Crocker et al (1999) on computational fluid dynamics (CFD) modeling of gas turbine combustor from compressor exit to turbine inlet, the detailed flow analysis was carried out for liner and wall temperature predictions. Hall et al (2014) Most of the previous studies are on a large-scale combustor employed in high power gas turbines. However, the large-scale combustors cannot be scaled down as it is due to unscalable parameters, such as characteristic combustion time (Van den Braembussche 2005).…”
Section: Introductionmentioning
confidence: 99%